18i-24x=6(-4x+9u)

Simple and best practice solution for 18i-24x=6(-4x+9u) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18i-24x=6(-4x+9u) equation:


Simplifying
18i + -24x = 6(-4x + 9u)

Reorder the terms:
18i + -24x = 6(9u + -4x)
18i + -24x = (9u * 6 + -4x * 6)
18i + -24x = (54u + -24x)

Add '24x' to each side of the equation.
18i + -24x + 24x = 54u + -24x + 24x

Combine like terms: -24x + 24x = 0
18i + 0 = 54u + -24x + 24x
18i = 54u + -24x + 24x

Combine like terms: -24x + 24x = 0
18i = 54u + 0
18i = 54u

Solving
18i = 54u

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '18'.
i = 3u

Simplifying
i = 3u

See similar equations:

| x+(.40)x=3 | | 44.83+0.05m=90 | | F(x)=x^2-12x+27 | | 38.12+0.20m=90 | | 7x-11=-4x-11 | | 4(x+1)-5(x+6)=3x+4 | | 3/16t=2 | | (5/9)k=2 | | y=2x-14+12 | | 6x^2+54x-60=0 | | (-2y)(-3x^2y^2)(-6xy^2)= | | ((x^2=2x)^1/3)-2 | | r^2+14r-207=0 | | -33-49v= | | 2x+45=113 | | -9-8b^2=-129 | | 450(x)+675(x)=6300 | | (6m)(-2n)= | | 41x^2=366 | | 16t^4-8t^2+1=0 | | D/200-D/220=2200 | | 4x^2-8x=-8 | | 8x^2+14x-42=0 | | 44425-125x+200x=45000-150x | | 4x^2-8c=-8 | | 7a^2+35a=0 | | 2x+(l+80)=180 | | 2x+(x+80)=180 | | 2x+x+80=180 | | 2x-3=7x-9 | | 81m^2+3=12 | | 33-7d=20 |

Equations solver categories